2015
DOI: 10.3402/gha.v8.26683
|View full text |Cite
|
Sign up to set email alerts
|

The health system consequences of agency nursing and moonlighting in South Africa

Abstract: BackgroundWorldwide, there is an increased reliance on casual staff in the health sector. Recent policy attention in South Africa has focused on the interrelated challenges of agency nursing and moonlighting in the health sector.ObjectiveThis paper examines the potential health system consequences of agency nursing and moonlighting among South African nurses.MethodsDuring 2010, a cluster random sample of 80 hospitals was selected in four South African provinces. On the survey day, all nurses providing clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 35 publications
0
27
0
2
Order By: Relevance
“…Overall, our findings were positive despite numerous occupational stressors that nurses are confronted with (Coetzee et al, 2013;Khamisa et al, 2013;Khamisa et al, 2017;Khunou, & Davhana-Maselesele, M., 2016;Wentzel & Brysiewicz, 2018) plus the challenges of moonlighting (Muller & Seekoe, 2014;Rispel & Blaauw, 2015). A possible explanation is that our respondents moonlighted in private hospitals.…”
Section: Work Engagementmentioning
confidence: 59%
See 1 more Smart Citation
“…Overall, our findings were positive despite numerous occupational stressors that nurses are confronted with (Coetzee et al, 2013;Khamisa et al, 2013;Khamisa et al, 2017;Khunou, & Davhana-Maselesele, M., 2016;Wentzel & Brysiewicz, 2018) plus the challenges of moonlighting (Muller & Seekoe, 2014;Rispel & Blaauw, 2015). A possible explanation is that our respondents moonlighted in private hospitals.…”
Section: Work Engagementmentioning
confidence: 59%
“…This "casualization" of the nursing workforce entails employing nurses on short-term contracts without benefits. There are different types of casual work arrangements: one is moonlighting, where nurses have a full-time and one or more temporary paid nursing job(s) (Rispel & Blaauw, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the second paper, Rispel and Blaauw examine the potential health system consequences of agency nursing and moonlighting among South African nurses ( 15 ). In the cross-sectional survey of 3,784 participants, 40.7% of nurses reported moonlighting or working for an agency in the year preceding the survey, 51.5% of all participants reported feeling too tired to work, 11.5% paid less attention to nursing work on duty, while 10.9% took sick leave when not actually sick in the preceding year ( 15 ). In a multiple logistic regression analysis, the differences between moonlighters and non-moonlighters were not statistically significant after adjusting for other socio-demographic variables.…”
Section: Themes and Focus Of The Special Issuementioning
confidence: 99%
“…Only one-fifth of agencies (21%) indicated that they conducted reference checks with past employers. Hence this is an area that needs improvement, because the failure of a nursing agency to conduct these basic quality checks could lead to serious negative incidents both for individual clients and for the health system as a whole ( 33 ).…”
Section: Discussionmentioning
confidence: 99%